Pengaruh Store Atsmosphere, Variasi Produk, dan Kualitas Pelayanan, terhadap Minat Beli Konsumen Vape Stores vs Karangjati, Kecamatan Bergas, Kabupaten Semarang - Wahyu Puji Pangestu; Ahmad Dwi Nurdiyanto; Riyono Riyono (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
the purpose of this research to determine and analyze the influence of Store Atmosphere (X1), product variety (X2), service quality (X3) on consumer buying interest (Y). The population in this study were all potential SVS Karangjati consumers, totaling 100 respondents. The type of research used is Non Probability sampling because the population is not yet known. Researchers then used purposive sampling focusing on consumers who bought at SVS Karangjati, with a quantitative approach. The analysis technique used is multiple linear regression using the Likert scale method. The research results can be concluded that : 1). Store Atmosphere has a positive and significant effect on consumer buying interest, 2). Product variety has a positive and significant effect on consumer buying interest, 3). Service quality has a positive and significant effect on consumer buying interest. Based on the results of this research, it would be better for the owner of SVS Karangjati to continue to maintain and improve his business, especially the store atmosphere, product variety and service quality so as to increase interest in buying among more potential consumers.